2014
DOI: 10.1371/journal.pone.0103012
|View full text |Cite
|
Sign up to set email alerts
|

A Phasin with Many Faces: Structural Insights on PhaP from Azotobacter sp. FA8

Abstract: Phasins are a group of proteins associated to granules of polyhydroxyalkanoates (PHAs). Apart from their structural role as part of the PHA granule cover, different structural and regulatory functions have been found associated to many of them, and several biotechnological applications have been developed using phasin protein fusions. Despite their remarkable functional diversity, the structure of these proteins has not been analyzed except in very few studies. PhaP from Azotobacter sp. FA8 (PhaPAz) is a repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 38 publications
2
43
0
Order By: Relevance
“…Generally PHAs are accumulated as light-refracting discrete granules inside the cell (123,124). These PHA granules can be stained specifically with Sudan black B or light fluorescent stains Nile blue A and Nile red ( Figure 4) (65,68,71,125,126).…”
Section: Structure Of Pha Granulesmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally PHAs are accumulated as light-refracting discrete granules inside the cell (123,124). These PHA granules can be stained specifically with Sudan black B or light fluorescent stains Nile blue A and Nile red ( Figure 4) (65,68,71,125,126).…”
Section: Structure Of Pha Granulesmentioning
confidence: 99%
“…Among the proteins associated to PHA granules, phasins constitute a very diverse group are the most dominant proteins of relatively small molecular size (124,140,141). A few that have been studied in detail revealed that they are associated with a structural role of PHA granules and may have several functions such as coating, stabilizing granules as structural proteins by non-covalently attached to the polyester core of granules ( Figure 5) (30,135,142,143,144) or activating genes and/or enzymes involved in PHA synthesis (124). Phasins promote PHA biosynthesis and their copy number has impact on PHA granule size (143,144).…”
Section: Structure Of Pha Granulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary-structure in silico predictions for phasins PhaP1 to PhaP4 from R. eutropha, PhaP1 from Ralstonia solanacearum, PhaP from Ralstonia metallidurans (17), PhaP Az (18), and PhaP Sp (12) revealed that these phasins have a high percentage (close to 90%) of amino acids in an ␣-helix conformation. This was found to be a general characteristic of phasins (18)(19)(20).…”
Section: Structural Aspects Of Phasinsmentioning
confidence: 99%
“…The same result was obtained when a plasmid expressing phaP was introduced in the cells, indicating that PhaP was able to complement the phenotypic effects caused by the groEL mutation in a manner similar to that for the GroELS protein. Although PhaP has no sequence or structure similarity to GroELS or to other chaperones (54), its capability to increase the tolerance of the groEL mutant to the chemicals tested further supports the possibility that this could be due to its chaperone-like properties.…”
Section: Discussionmentioning
confidence: 94%